Comment on 'Growth Empirics and Reality,' by William A. Brock and Steven N. Durlauf - Pritchett, Lant (Washington, DC: World Bank, 2014)
World Bank economists are mostly practical people, people who try to answer the question, 'what exactly should this particular country do right now?' But if they had hoped that the growth regression lessons summarized in William Brock and Steven Durlauf's article would enhance their practical advice giving, they might feel some dissatisfaction. How would they change their advice to, say, Brazil? But that is why this article is important conceptually. It goes to the heart of the matter by proposing a change in the empirical growth literature's fundamental methodology, from model testing to decision theoretic. The article's valiant but flawed attempt reveals the difficulties in making this shift, however. The reader likes to make three points: there is a tension between the interests of academics and practitioners in growth regressions; output response heterogeneity is a huge practical problem; and policy decisions can be guided only in broad outlines by growth regressions.